Consumption patterns in Kuala Lumpur: how does B40 group prioritizating needs - Nur Jannah Bukhari (Penerbit Universiti Kebangsaan Malaysia, 2024)
Expenditure involves allocating money to various items or services to satisfy our needs from different aspects of life. To understand the consumption and expenditure patterns, this study aims to analyze the spending habits of the B40 youth group living in urban areas, specifically in Kuala Lumpur, by examining their specific needs. To achieve the objectives of this study, a research framework on the prioritized needs during shopping or expenditure has been established. These needs include basic needs, protection and health, family, religion, and leisure. Subsequently, the findings of the study indicate that there are differences in priorities during shopping were found, as indicated by respondents to ensure survival in the city. Although basic needs such as home ownership are often discussed, the unaffordability of prices, especially in urban areas, has resulted in home buying not being a major contributor to expenditure breakdowns. This suggests that the type of settlement contributes to the lifestyle and spending habits practiced by youth in urban areas. This study demonstrates that urbanization can affect how youth allocate their money to sustain their livelihoods.